Frottage and toucherism, voyeurism and coitus interruptus yield to skin glowing in male - Lorenzo Martini (Our Dermatology Online, 2023)
Since a patient had recounted to the A (he means a bien agé gentleman) that when he was younger., had noticed that a flic in Paris, who was imposing to him a fine for speeding, tried to hide an odd and unjustifiable penis erection beneath his trousers, the A has been brooding that that phenomenon was reputable a paraphilia that could reveal even other psycological and physiological conditions in man.(many novelists have written that when Nazis used to shoot dissidents and homosexulas in the extermination camps, showed awkwardly erections underneath their uniforms). Manifold are the paraphilias, from the simplest masturbation to the voyeurism, from the frottage to the toucherism, and the A discovered that these mental statuses could imply some hidden manifestations and/or benefits to health and skin beauty.